Prevalence and predictors of macrosomia newborn : Northern-Norwegian mother-and-child study - Islam, Md Rakibul (Universitetet i Tromsø, 2012)
BACKGROUND The prevalence of macrosomia newborn has increased in Norway over the last few decades. In Norway, there is ample evidence that macrosomia is associated with elevated risk of complications both for the mother and the newborn. It is also evident that being born macrosomic is associated with future health risks. OBJECTIVE The Study was aimed to understand the prevalence and predictors of macrosomic newborn in the three northern counties of Troms, Finnmark and Nordland in Norway. METHODS Using data from The North Norwegian Mother-and-Child Cohort Study (MISA), 479 pregnant women who delivered their babies were included in this study. A simple questionnaire was administered to obtain personal information about current diet, smoking, and alcohol habits, medication and dietary supplements. Maternal weight was also measured while self-reported pre-pregnancy weight and height were collected from pregnant women. Permission was also obtained to consult their medical records. RESULTS Mean birth weight and body mass index of children were 3617g (SD 493) and 14.27 (SD 1.22) respectively. Macrosomia (birth weight ≥4,000g) was observed among 101 (21.2%) newborns. Significant association between macrosomia and pre-pregnancy maternal weight, smoking at the beginning and at the end of pregnancy were observed in a bivariate analysis. Logistic regression analysis showed that maternal pre-pregnancy weight was a strong predictor of macrosomia among the included women. Non-smoking at the end of pregnancy was another significant determinant of macrosomia observed in regression analysis. CONCLUSION Pre-pregnancy maternal weight was the most important predictor of macrosomia for the newborn baby. General pre-pregnancy health advise and dietary advise for young women will have a very positive impact on pregnancy outcome.